The comparison of three different correction formulas and the modified Ehler’s algorithm in the evaluation of intraocular pressure after LASIK - Cicek, Ayse; Atas, Mustafa; Melek Ulusoy, Dondu; Vural, Esra; Bedirhan,; Alabay,; Aydin, Ismail; Cobanoglu, Hayrettin (Annals of Medical Research, 2021)
Aim: The aim of this study is to assess the correlation between the preoperative intraocular pressure (IOP) and the postoperative corrected IOP values calculated by using the modified Ehler’s algorithm and the three formulas after laser asisted in situ keratomileusis (LASIK) surgery.Material and Methods: The medical records of the patients to whom LASIK was performed to correct myopia and/or astigmatism between June 2018 and December 2018 were analyzed. The corrected preoperative and postoperative IOP values calculated with modified Ehler’s correction factor algorithm were compared. In addition, the corrected postoperative IOP values were calculated with Formula 1, Formula 2 and Formula 3 and the corrected postoperative IOP values were compared with the uncorrected preoperative IOP. Paired t-test was performed to compare the preoperative and postoperative IOP values. The Pearson correlation coefficients were calculated to analyze the correlation between preoperative IOP values and postoperative corrected IOP values.Results: The statistically significant difference was not observed between preoperative IOP and postoperative corrected IOP for formula two and formula 3 (p=0.42 and 0.80, respectively). There was significant difference between preoperative and postoperative IOP corrected with modified Ehler’s algorithm (p=0.03). In addition, a significant difference between preoperative IOP and postoperative IOP corrected with formula 1 was observed (p0.01). The mean of the difference between preoperative IOP and postoperative IOP corrected with formula was 3.1±1.4 mmHg (ranging 1.99 to 4.35 mmHg) and the mean of the difference between preoperative and postoperative IOP corrected with modified Ehler’s algorithm was 1.4±1.5 mmHg (ranging 0.1 to 2.6 mmHg). There was no correlation between preoperative IOP and postoperative corrected IOP values for Ehler algorithm and three formulas.Conclusion: Formulas 2 and 3 could be used to acquire a hint about the increased IOP, but none of them is the exact way to assess IOP correctly following LASIK. There is need for new solutions in this field. Keywords: LASIK; intraocular pressure; correction formula; the modified Ehler’s algorithm.
Keywords: LASIK; intraocular pressure; correction formula; the modified Ehler’s algorithm.